Dosimetric Study at the Adult Subjects in Standard Radiography of the Neurological System at the Regional Hospital of Ngaoundr, Cameroun (Global Journal of Medical Research, 2018)
Abstract not found
Keywords: standard radiography; entrance dose; radioprotection; diagnostic reference level (DRL)